Security and development: Role of the Nepali Army in nation building - Adhikari, Sonika (Unity Journal, 2020)
This paper aims to highlight the integral role of Nepali Army towards national security and development. The researcher has applied secondary source of research design to collect the information. The result suggested that the Nepali Army played a major role in the formation as well as the development of Nepal as a strong stable nation–state. For the national security, the Nepali Army had fought many battles. Their contribution was visible from the unification campaign initiated by Prithvi Narayan Shah in 1740 AD to the Nepalese Civil war fought between the Communist Party of Nepal and the government of Nepal from 1996 to 2006. Similarly, for the development of the nation, their role is visible in infrastructure development, building civil military relation, disaster management, nature conservation and so on. Nepali Army along with the national security has been expanding its role in sectors like education, health and recreation with the interest of serving the people.